교사 산림교육 직무연수 프로그램 효과성 분석 - 이윤주; Yoon Joo Lee; 하시연; Si Yeon Ha; 최선혜; Seon Hye Choi; 이연희; Yeonhee Lee (한국산림과학회지, 2020)
본 연구는 2017년 8월 국립횡성숲체원에서 진행된 교원 산림교육 직무연수에 참가한 유치원 및 초ㆍ중ㆍ고등학교교사 46명을 대상으로, 사전ㆍ사후 설문조사를 통해 프로그램의 효과성을 분석한 것이다. 연구결과, 직무연수 참여 전과 후에 교사들의 환경감수성과 자연친화적 교수태도, 교사효능감이 통계적으로 유의하게 상승하여, 프로그램의 긍정적인 효과를 확인할 수 있었다. 그러나 교사효능감과 관련해 교사의 자신감은 다소 줄어든 것으로 나타나, 교사들이 자신감을 가질 수 있는 실질적인 교수역량 개발을 위한 연수의 필요성이 확인되었다. 본 연구는 학교 현장에서 학생들의 환경감수성과 자연친화적 태도 발달에 중요한 영향을 미치는 교사들을 대상으로 산림교육의 효과성을 확인하고, 보다 효과적인 직무연수 프로그램을 개발하기 위한 시사점을 도출하였다는 데 의의가 있다. This study analyzed the effectiveness of the forest education program for teacher training. The training program was conducted at the National Center for Forest Activities, in Hoengseong, Korea in August 2017. Presurveys and postsurveys were administered to 46, K-12 teachers who participated in the forest education program. The results showed a statistically significant increase in the teachers’ environmental sensitivity, eco-friendly teaching attitude, and teacher efficacy after the program. Survey participants expressed a slightly lower confidence in terms of teacher efficacy after participating in the program. This confirms the need for a training program with a focus on practical teaching skills, which would help teachers become more confident in providing forest education. This study verifies the effectiveness of the forest education program for teachers, who play an important role in developing students’ environmental sensitivity and eco-friendly attitude. Furthermore, it suggests the need to develop more effective forest education programs for teacher training.